Emotional drivers of pedagogy and their place in the motivational process: distinguishing percepts from outcomes - Porter, Karen; Donaldson, David Ian (Frontiers in Education, 2025)
IntroductionResearch examining teachers’ experiences during the Covid pandemic highlighted the importance of emotion as a driver of motivation, specifically the emotions of CARE, CURIOSITY, COOPERATION and CHALLENGE. Here we examine the generalisability of those findings in the post-pandemic period.MethodsInterviews were carried out with a new cohort of nine Scottish teachers, and deductive thematic and narrative analyses were used to analyse the data.ResultsResults confirmed the presence of the four motivating emotions, as distinct from outcome emotions such as pride and frustration. However, their prevalence shifted, with CARE and CURIOSITY less dominant than during Covid, while CHALLENGE was more prevalent. Teachers’ accounts also suggested that COMMUNITY is a more accurate label than COOPERATION for capturing the feelings associated with shared social motivation. Examination of co-occurrence of emotions showed they were frequently mentioned in close temporal proximity to each other. Narrative analysis highlighted individual stories that link emotional percepts, cognitions, volitional behaviour, and outcome emotions within each teacher’s situational context. We consequently propose a motivational process model consisting of these four factors, in contrast to a recent integrative framework including six stages of action in which emotions are less foregrounded.DiscussionWe discuss how these findings support the development of a Theory of Emotionally Motivated Pedagogy that presents emotions as a central component of teacher motivation. Implications are discussed for pedagogical practitioners seeking to understand their own motivation, as well as for researchers examining motivation as a complex affectivist phenomenon.